Animal vaccines: failures and adverse events - Tizard, Ian (Henry Stewart Talks, 2019)
Causes of vaccine failure, Immune responses to vaccines, Effect of maternal immunity, Adverse events, Effect of dog size on immune responses and adverse events, Type 1, 2 and 3 hypersensitivity reactions